Giant cell fibroblastoma: a case report - Hrudka, Jan; Hojný, Jan; Leamerová, Eva; Matěj, Radoslav (Ceskoslovenska patologie, 2022)
Giant cell fibroblastoma is a rare locally aggressive tumor of subcutaneous mesenchymal tissue, occurring mostly on the trunk in young individuals with maximal incidence in the first decade of life. Local recurrences of giant cell fibroblastoma are common if marginally excised, however, distant metastases do not occur. Giant cell fibroblastoma was labelled as a juvenile variant of dermatofibrosarcoma protuberans (DFSP) due to quite frequent combination of both lesions, morphological similarities, identical immunoprofile, and shared gene fusion t(17;22) COL1A1-PDGFB. In this paper, we report a case of a young man with a slowly growing subcutaneous tumor in the groin. The tumor was excised and histological examination identified a mesenchymal tumor with variable cellularity, presence of multinucleated giant cells and pleomorphic spindle cells, which lined pseudovascular or angiectoid spaces. The CD34 immunohistochemistry showed strong positivity in all of these cells, whereas ERG was positive only in endothelial cells in true vessels. These findings led to a suspicion on giant cell fibroblastoma. Because of its borderline malignant behaviour and positive surgical margins, the lesion was subsequently reexcised. The molecular analysis identified the transcription product of gene fusion COL1A1-PDGFB and thus, final diagnosis was confirmed. The article includes review of the literature and brief historical overview of giant cell fibroblastoma concept as an unique entity.
Keywords: juvenile; Dermatofibrosarcoma; Giant Cells; Proto-Oncogene Proteins c-sis; giant cell; mužské pohlaví; protoonkogenní proteiny c-sis; Humans; obrovské buňky; nádory kůže; dermatofibrosarkom; endoteliální buňky; Skin Neoplasms; dermatofibrosarcoma protuberans; lidé; Male; Endothelial Cells; fibroblastoma